2022
DOI: 10.1103/physrevlett.128.065001
|View full text |Cite
|
Sign up to set email alerts
|

Low-Threshold Induced-Side-Scattering Instability at the Tokamak Edge Transport Barrier Predicted in O-Mode Electron Cyclotron Resonance Heating Experiments

Abstract: The possibility of electron plasma waves trapping in the steepest part of the tokamak's edge transport barrier leading to the excitation of low-threshold side-scattering absolute parametric decay instability in ordinary mode electron cyclotron resonance heating (ECRH) experiments is demonstrated. The instability is shown to be important for ECRH experiments in ITER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, these waves can be also localized along the magnetic field because of a magnetic ripple whereas their group velocity in the third direction tends to zero. This combination of properties should result in their easy parametric excitation in ITER [26]. The predicted effect deserves experimental investigation at the present day tokamaks in regimes with the ETB.…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, these waves can be also localized along the magnetic field because of a magnetic ripple whereas their group velocity in the third direction tends to zero. This combination of properties should result in their easy parametric excitation in ITER [26]. The predicted effect deserves experimental investigation at the present day tokamaks in regimes with the ETB.…”
Section: Introductionmentioning
confidence: 81%
“…For instance, PDIs involving X-mode radiation reaching the UHR are being considered for generating fast ions with ECRH in spherical tokamaks [7,8], although we note that the efficacy of this scheme has yet to be demonstrated, and trapped UH wave PDIs occurring near the plasma edge have already been used to investigate edge-localized mode and L-mode blob characteristics at ASDEX Upgrade [6]. Since PDIs involving low-frequency trapped waves in the density pedestal are expected in connection with O-mode ECRH at ITER [60], it would be of particular interest to assess their value as an edge diagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, decay of an O-mode ECRH wave to a trapped UH wave and a low-frequency lower hybrid wave has been investigated theoretically [53][54][55][56], in a lowtemperature plasma filament [3], and at the FTU tokamak [57][58][59]. Additionally, it has recently been suggested that trapped low-frequency waves existing as a consequence of the strong gradients in the ITER and ASDEX Upgrade pedestals could lead to PDIs near the plasma edge during O-mode ECRH [60]. In this Paper, we review the basic conditions under which the above PDIs may occur and assess their relevance for the O-mode ECRH scenarios proposed for ITER [12], in a manner similar to the investigations in Section 4 of [1], but covering different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Until very recently the propagation and absorption of O-mode microwaves were believed to be well-described by the linear theory and assumed to be predictable in detail. However, as it was shown in [1], in ITER they can suffer from a low threshold induced scattering parametric decay instability (PDI) in the edge transport barrier (ETB). The presence of a large density gradient have a significant impact on the properties of waves in the lower hybrid (LH) frequency range, leading to new transparency windows that are absent in a homogeneous plasma [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…, pr  of the non-linearly excited LH or EP wave starts to grow in the pump localization zone and experiences diffraction along y . According to[1], this phenomenon is described by the following equation 22…”
mentioning
confidence: 99%